Why are sustainable practices often elusive? The role of information flow in the management of networked human-environment interactions. (January 2023) - Crabtree, Stefani A.; Kahn, Jennifer G.; Jackson, Rowan; Wood, Spencer A.; McKechnie, Iain; Verhagen, Philip; Earnshaw, Jacob; Kirch, Patrick V.; Dunne, Jennifer A.; Dugmore, Andrew J
Graphical abstract: Highlights: The EnIfPe model assesses how limitations impacted information flow in past societies. Poor information flow led to compromises in sustainable practices. The dimensions of our lived environment shape our ability to wield information. Archaeological cases are essential for contemporary debates on sustainability. Abstract: Analyzing the spatial and temporal properties of information flow with a multi-century perspective could illuminate the sustainability of human resource-use strategies. This paper uses historical and archaeological datasets to assess how spatial, temporal, cognitive, and cultural limitations impact the generation and flow of information about ecosystems within past societies, and thus lead to tradeoffs in sustainable practices. While it is well understood that conflicting priorities can inhibit successful outcomes, case studies from Eastern Polynesia, the North Atlantic, and the American Southwest suggest that imperfect information can also be a major impediment to sustainability. We formally develop a conceptual model of Environmental Information Flow and Perception (EnIFPe) to examine the scale of information flow to a society and the quality of the information needed to promote sustainable coupled natural-human systems. In our case studies, we assess key aspects of information flow by focusing on food web relationships and nutrient flows in socio-ecological systems, as well as the life cycles, population dynamics, and seasonal rhythms of organisms, the patterns and timing of species' migration, and the trajectories of human-induced environmental change. We argue that the spatial and temporal dimensions of human environments shape society's ability to wield information, while acknowledging that varied cultural factors also focus a society's ability to act on such information. Our analyses demonstrate the analytical importance of completed experiments from the past, and their utility for contemporary debates concerning managing imperfect information and addressing conflicting priorities in modern environmental management and resource use.